Habiter la distance – la democratie anti-mimetique de Rousseau - Vinolo, Stéphane (2017)
In the texts of René Girard there is an undeniable mistrust of democracy. Girard notes that democracy is the regime that favours the violent side of mimesis, that is, internal mediation. In Jean-Jacques Rousseau’s texts, both the highly relevant analysis of self-esteem or envy, which literally makes us live under the gaze of others, and a true eulogy of democracy appear.